2011
DOI: 10.1021/om200715w
|View full text |Cite
|
Sign up to set email alerts
|

Crowded Diphosphinomethane Ligands in Catalysis: [(R2PCH2PR′22P)NiR″]+Cations for Ethylene Polymerization without Activators

Abstract: The preparation of a series of nickel dichloride complexes with bulky diphosphinomethane chelate ligands R2PCH2PR′2 is reported. Reaction with the appropriate Grignard reagent leads to the corresponding dimethyl and dibenzyl complexes. Cationic monomethyl and mono-η3-benzyl complexes are generated from these dialkyl complexes by protonation with [H­(OEt2)2]+[B­(3,5-(CF3)2C6H3)4]−, while the complex [(dtbpm-κ2 P)­Ni­(η3-CH­(CH2Ph)­Ph]+[B­(3,5-(CF3)2C6H3)4]− is obtained from protonation of the Ni(0) olefin compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
3
23
0
Order By: Relevance
“…However, this value is smaller compared to other tetrahedrally coordinated Ni II compounds that have magnetic moments within the range of μ eff =3.3–4.0 μ B [29] . On the other hand, complexes of [NiX 2 L] (X=Cl, Br, I; L=bis‐diphosphines) are mainly described to be diamagnetic caused by the square planar geometry [7, 8, 30] …”
Section: Resultsmentioning
confidence: 91%
“…However, this value is smaller compared to other tetrahedrally coordinated Ni II compounds that have magnetic moments within the range of μ eff =3.3–4.0 μ B [29] . On the other hand, complexes of [NiX 2 L] (X=Cl, Br, I; L=bis‐diphosphines) are mainly described to be diamagnetic caused by the square planar geometry [7, 8, 30] …”
Section: Resultsmentioning
confidence: 91%
“…Single crystals of 7·PPh 3 and 7·P i Bu 3 were grown from a saturated THF and toluene solutions, respectively. The solid-state structures, depicted in Figure , indicate they are square planar and exhibit characteristic Ni–C bonds (1.929(3) Å for 7·PPh 3 and 1.935(3) Å for 7·P i Bu 3 ), similar to known complexes. ,, The different steric profiles of phosphine ligands does not have a significant influence on the bond angles, with a N(2)–Ni(1)–C(1) angle of 168.5(1)° for 7·PPh 3 and 166.9(1)° for 7·P i Bu 3 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…His research interests combined all three fields, with a focus on homogeneous catalysis with transition metal complexes. Bidentate donor ligands with a small bite angle such as bis(di- tert -butylphosphino)methane (dtbpm) were a unique feature of his work [61,67,7072 8081 84,86,9394 97,100101 103,107,124,128,148149] that ultimately enabled C–Si activation of organosilanes and the C–C activation of oxiranes by coordinatively unsaturated platinum species [66,149]. In the mechanism of the Dötz reaction, he found that chromacyclobutene structures were unrealistic intermediates and instead proposed vinylcarbene complexes as much more stable isomers [64,68,88].…”
Section: Peter Hofmann a Multifaceted Organometallic Chemistmentioning
confidence: 99%